Silsilatu al ghidhaai al ghareebah - Capeci, Anne.; Speirs, John; Cole, Joanna; Degen, Bruce (New York : Scholastic, 2006)
Arnold, a reluctant pupil of Ms. Frizzle, goes on a field trip on the Magic School Bus with the rest of the class, including his annoying cousin Janet, and as they learn about ecosystems, Arnold realizes that he is learning a lot about food chains.
Text in Arabic.
3-6
Based on The Magic School Bus books written by Joanna Cole and illustrated by Bruce Degen.
Title supplied by OCLC WorldCat.
Keywords: School field trips -- Fiction; Food chains (Ecology) -- Fiction; Arabic language materials; Cousins -- Fiction; Field trips -- Fiction; Food chains (Ecology) -- Fiction; Arabic language; Cousins -- Fiction